AMBIVALENSI DEMOKRASI DI INDONESIA TERHADAP KEBEBASAN BERPENDAPAT (ANALISIS PASAL 28 UUD 1945 - Nur, Muhammad Tahmid; Herianto, Herman (Datuk Sulaiman Law Review (DaLRev), 2022)
:   Democracy is a form of government system that has the nature of freedom of every citizen to maintain, regulate and protect from coercion of the body entrusted to govern. The problems in this thesis are (1) How is the ambivalence of democracy in Indonesia towards freedom of expression? (2) How is Article 28 of the 1945 Constitution applied to the ambivalence of democracy in Indonesia? This type of research is literature research using references from books on democracy, Islamic views on the ambivalence of democracy and the 1945 Constitution which discusses the implementation of democracy in Indonesia. The data collection technique used is to collect historical data on democracy in Indonesia from books that discuss the implementation of democracy by using hiztoris theory analysis up to the present time. The results of the research are that the application of Pancasila democracy is a bridge for the community to be able to convey what is a complaint in social life, as regulated in Article 28 of the 1945 Constitution is that everyone has the right to freedom of association, assembly, and expression of opinion as referred to in one form of the implementation of human rights in the 1945 Constitution. The implementation of democracy should be more aware of the government in the country so that democratic ambivalence can be prevented and become an important role for the running of democracy, the existence of democracy is a bridge for conveying people's aspirations as freedom of opinion and legal protection influential in the Indonesian constitutional structure and its role is very important in advancing the Indonesian nation.